Theistic metaphysics in the postmodal era - Lo, T-C (2021)
This thesis will provide a distinctive way of doing theistic metaphysics in light of the recent postmodal revolution in metaphysics. In Chapter I, I will undertake the preliminary task of figuring out what metaphysical tools we may need in the inquiries of theistic metaphysics. I will propose three postmodal concepts for theistic metaphysicians: (i) the concept of grounding, (ii) the concept of divine causation, and (iii) the concept of structure. In Chapter 2, I will go through various issues with regard these postmodal concepts including their formal properties and their relations to each other, before applying them to first-order questions in theistic metaphysics. After the second-order reflections on the postmodal concepts in question, I will turn to their applications in Chapters 3-5. The focus of Chapter 3 is theistic accounts of properties. I will demonstrate how various theistic accounts of properties may be formulated in terms of these postmodal concepts. I will also propose my own theistic account of properties which draws on some metaontological considerations raised in this chapter. In Chapter 4, I will turn to issues regarding theistic accounts of modality. I will show how the postmodal concepts may shed new light on several traditional questions about God and modality. A number of theistic accounts of modality will then be evaluated from a postmodal perspective. In Chapter 5, the postmodal concepts will be applied to issues with regard to God and time. I will defend the coherence of various positions about the relationship between God and time. In short, Chapters 3-5 will demonstrate how these postmodal concepts may help formulate, clarify, and answer various first-order questions of theistic metaphysics. Finally, in Chapter 6, I will summarize the previous chapters and say something about the limits of the postmodal approach proposed in this thesis.